Agile management and its Role in Achieving Sustainable Performance: A Case Study of the Cordoba Bridge Project in Baghdad (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to measure the level of awareness and adoption of the agile methodology among project managers in the Iraqi environment. And then analyze the impact of the axes of agile management of projects and sustainable performance used on the performance of the Department of Roads and Bridges, where the researcher used checklists to support the case study, prepared for this purpose a questionnaire consisting of (49) items, and was applied in the Cordoba Bridge project to extract the knowledge and skill gaps of the axes related to (agile management of projects, sustainable performance). The study found that agile project management is of particular importance in dealing with projects in a more effective way by identifying unexpected risks and changes before they occur and then helping to design projects according to these risks and future changes.